CRISIS INTERVENTION APPROACHES IN SOCIAL WORK:EVIDENCE BASED PRACTICE FROM A SYSTEMATIC LITERATURE REVIEW PERSPECTIVE - Meiti Subardhini; Sabar Riyadi (Adisam Publisher, 2026)
This study aims to analyze crisis intervention approaches in social work based on evidence based practice through a systematic review of scientific literature published between 2010 and 2025. The method employed is a Systematic Literature Review (SLR) following the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta Analyses) guidelines. Data sources were obtained from international databases (Scopus, SpringerLink, Taylor & Francis, ProQuest, PubMed, and Google Scholar) and national databases (Garuda and Neliti). Out of a total of 785 identified articles, 25 met the inclusion criteria and were analyzed using a thematic approach. The findings reveal four major crisis intervention models commonly applied in social work practice: Roberts’ Seven Stage Crisis Intervention Model, Task Centered Practice (TCP), Crisis Oriented Family Therapy, and the Community Crisis Response Model. The Roberts model was found to be effective in reducing acute stress symptoms and enhancing individual coping skills; TCP demonstrated strengths in time efficiency and client engagement; crisis oriented family therapy successfully reduced relational conflicts; while community based models contributed to increased resilience and social solidarity. These findings underscore the importance of integrating evidence based approaches into social work education, practice, and policy development in Indonesia. Further local research is needed to adapt crisis intervention models to Indonesia’s socio cultural context, as well as to formulate national policies that establish standard operating procedures for crisis intervention across various social service settings.